PENGARUH STRUKTUR MODAL, PROFITABILITAS, LEVERAGE, DAN PRICE EARNING RATIO (PER) TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2017-2019 - Widya Dwi Mardiana; Moh. Amin; Hariri Hariri (e_Jurnal Ilmiah Riset Akuntansi, 2020)
ABSTRACTThis research was conducted to determine the effect of capital structure, profitability, leverage, and price earning ratio to the value of the company at manufacturing companies listed on the Indonesia Stock Exchange 2017-2019 period. The data used is secondary data. In this study the data analysis method used is multiple linear regression. The sampling technique uses a purposive sampling technique and obtained 35 manufacturing companies that fit the sample criteria that will be used as the object of research. Based on the test results that simultaneously capital structure variables, profitability, leverage, and price earning ratio have a significant effect on firm value. Partially shows that capital structure and profitability variables have a significant effect on firm value, while leverage and price earning ratio variables have no significant effect on firm value.Keywords: Capital Structure, Profitability, Leverage, Price Earning Ratio, and Company Value